Judicial Review Implementation On Dissenters Notary Rights In Making Deeds - Binta Istiqlaly; Umar Ma’ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) Knowing and analyzing on the Implementation of the Right Dissenters in the Making Notary Deed. 2) To determine and analyze about the obstacle Notaries in Implementing Dissenters rights. The method used in this research is the empirical jurisdiction. Adopting legislation, learning materials primary and secondary law. The technique of collecting data using interviews and literature study and data analysis techniques qualitative analysis using descriptive analysis decomposition.After doing research Juridical Review of Implementation of the Right Dissenters In the Manufacture Notary Deed to a conclusion that is Implementation of the Dissenters rights in the Making Notary Deed is basically the right to withdraw from testifying upfront Court in Civil and Criminal problem. Implementation of the right of refusal notaries in practice, if it turns out the notary as a witness or a suspect, defendant, or in the examination by the Board of Trustees Notary divulge and provide information/statements should shall be kept confidential, while legislation is not ordered, then the complaint filed by parties who feel aggrieved can sue the notary.As well as Obstacles Notaries in options or Use Dissenters rights in the Making Deed is faced by a notary public in using the right of refusal which are the Assembly, Regional Supervisor (MPD) approved the request of the police in the inspection of a notary public, a notary unable to escape to does not provide information because the police already have the recommendation of the Supervisory Council of Regions (MPD). Another constraint is that if the investigating authorities in this case the police use forceful measures with the reason for the interest of the investigation, the notary can not usually be avoided by reason of use right of refusal because the police could have used the excuse that the notary was not cooperative in providing information regarding the deed he made , so that the police do a forced effort.Keywords: Dissenters Rights, Notary and Deed.